Impact of the pan-genome of Escherichia coli on the potential for de novo antibiotic resistance evolution: Supplemental material - Jagdmann, Jennifer (Uppsala University, 2022)
Data consists of Table and Figure relating to the article "Impact of the pan-genome of Escherichia coli on the potential for de novo antibiotic resistance evolution".

The dataset was originally published in DiVA and moved to SND in 2024.

Data består av Tabell samt Figur tillhörande artikeln "Impact of the pan-genome of Escherichia coli on the potential for de novo antibiotic resistance evolution".

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Impact of the pan-genome of Escherichia coli on the potential for de novo antibiotic resistance evolution: Supplemental material
Keywords: microbiology; mikrobiologi; antibiotic resistance; antibiotikaresistens; Escherichia coli; kolibakterier; Microbiology; Mikrobiologi